The Dynamics of three species food web model with disease in the intermediate predator - Naji, Raid Kamel; Mustafa, Arkan N (Sulaimani Journal for Pure and Applied Sciences, 2013)
An eco-epidemiological model consisting of a three-species food web model, with an SIS epidemic disease in the intermediate predator, is proposed and analyzed. It is assumed that the disease transmitted between the individual of intermediate predator species only through an external factors as well as contact. The existence, uniqueness and boundedness of the solution of the system are studied. The existence of all possible equilibrium points are discussed. The local as well as global stability analysis of each equilibrium point is investigated. Finally further investigations for the global dynamics of the proposed system are carried out with the help of numerical simulations. It is observed that the system has one type of attractors, its approaches asymptotically to one of its equilibrium points.
Keywords: Food web model; SIS epidemic disease; Stability; Lyapunov function